PASH: STROMAL AND PSEUDOANGIOMATOUS HYPERPLASIA — SURGICAL TREATMENT USING ONCOPLASTIC TECHNIQUES — THOREK AND DERMAL FLAP - Mendonça, Ana Carolina Guglielmelli; Andrade, Raffaela Levy de; Pires, Douglas de Miranda (Mastology, 2018)
Pseudoangiomatous stromal hyperplasia (PASH) is a benign and infrequent mammary pathology, characterized by abnormal proliferation of stromal cells forming a complex network of channels interconnected by vascular spaces, delineated by fusiform cells, originating from myofibroblastic cells. It is commonly found in breast biopsies as an incidental finding and, more rarely, it can form a nodular, tumorlike mass or exhibit a pattern of diffuse involvement of the breast parenchyma. It affects women aged between 18 and 45 years old and is related to hormonal stimulation. In most cases, PASH shows slow growth. The treatment recommended by most authors is a broad excision of the lesion, with free margins to avoid local recurrences. Surgical resection combined with breast reconstruction techniques allows the incorporation of concepts and techniques that respect aesthetics and improve women’s quality of life. This study aimed to report the case of a 40-year-old patient with multiple bilateral breast nodules, associated with ptotic hypertrophic mastopathy, treated by adenectomy and immediate reconstruction with mammary prosthesis using Thorek’s technique. The patient presented a good postoperative evolution, with excellent cosmetic results and no evidence of disease after 19 months of diagnosis.